The Relationship between the Activity Balance Confidence and Mobility Tests among Older Adults in Indonesia. (4th July 2022) - Susilowati, Indri Hapsari; Sabarinah, Sabarinah; Nugraha, Susiana; Alimoeso, Sudibyo; Hasiholan, Bonardo Prayogo; Pengpid, Supa; Peltzer, Karl
Abstract : Introduction . Unsteady gait, instability, and lower extremity muscle weakness are some of the risk factors for falls. Reduced balance is a further precursor of falls, and injuries adversely affect the instability. In doing an activity without losing their balance, confidence among older adults is also crucial because it will influence their mobility. Objectives . The objective of this study is to examine the association between activity balance confidence and functional mobility, including gait, balance, and strength, among older adults. Methods . A cross-sectional study was conducted among older adults living in long-term care facilities and community dwellings. A total of 326 older adults (>60 years old) participated in this study from three provinces in Java Island, Indonesia. The inclusion criteria were older adults living independently and without obstacles in communication, who have no hearing loss, and who agreed to be respondents. The activity-specific balance confidence (ABC) scale determines the level of confidence. The participants were asked about their balance confidence not to lose their balance while doing 16 activities. The dependent variable is the mobility test, including a gait test using TUG (times up and go) to see how the subjects stand, walk, and turn around; a balance test (four stages); and a strength test (30-second chair stand). Results . The results of the ABC scale showed the respondents felt the most confidence not to lose their balance when they walk around the house (82.01%) and the less confidence when they stepped onto or off an escalator while holding onto a railing (37.7%). The gait, balance, and strength test revealed that 51.2% of the respondents showed an unsteady gait, 63.8% showed instability that felt awkward and unusual when standing on one leg, and 60.1% of the participants showed muscle weakness. The bivariate analysis significantly correlated the ABC scale test and all mobility tests. The older adult participants who are not confident will have 12.03 times higher the unstable result of the gait test, 8.4 times higher the unstable result of the balance test, and 7.47 times higher the less strength result of the strength test who are confident. Conclusion . Older adults who lack balance confidence showed significantly poorer results in mobility tests.